"We're not dead yet!": Extreme energy and transport poverty, perpetual peripheralization, and spatial justice among Gypsies and Travellers in Northern Ireland. (May 2022) - Sovacool, Benjamin K.; Furszyfer Del Rio, Dylan D.
Abstract: Even though a place to call home may be a fundamental human right, Gypsies and Travellers often confront some of the poorest health outcomes of any group in society, face almost constant accommodation insecurity, and reside in living environments with very poor conditions or high levels of social intolerance. Based on extensive original research with Gypsies and Travellers in Northern Ireland, this study explores their housing and energy needs, transport and mobility patterns, and challenges to their overall health and quality of life. Our investigation revolves around three core thematic areas. In exploring the theme of extreme and recurring poverty and vulnerability, we reveal not only problems but coping strategies and patterns of community resilience. In exploring the theme of perpetual peripheralization, we reveal troubling patterns of intolerance, discrimination, and cultural antagonism. In exploring our theme of spatial justice, we discuss mechanisms to improve the quality of life and energy and mobility outcomes for this marginalised group. Highlights: Gypsies and Travellers are one of the most marginalised groups in society. We explore their housing and energy needs, transport and mobility patterns, and challenges to health. We reveal problems and coping strategies, and patterns of community resilience. We reveal troubling patterns of intolerance, discrimination, and cultural antagonism. We discuss mechanisms to improve the quality of life and energy and mobility outcomes.